Myelin Water Imaging Demonstrates Lower Brain Myelination in Children and Adolescents With Poor Reading Ability - Beaulieu, Christian; Yip, Eugene; Low, Pauline B.; Mädler, Burkhard; Lebel, Catherine A.; Siegel, Linda; Mackay, Alex L.; Laule, Cornelia (Frontiers in Human Neuroscience, 2020)
Magnetic resonance imaging (MRI) provides a means to non-invasively investigate the neurological links with dyslexia, a learning disability that affects one’s ability to read. Most previous brain MRI studies of dyslexia and reading skill have used structural or diffusion imaging to reveal regional brain abnormalities. However, volumetric and diffusion MRI lack specificity in their interpretation at the micro-structural level. Myelin is a critical neural component for brain function and plasticity, and as such, deficits in myelin may impact reading ability. MRI can estimate myelin using myelin water fraction (MWF) imaging, which is based on evaluation of the proportion of short T2 myelin-associated water from multi-exponential T2 relaxation analysis, but has not yet been applied to the study of reading or dyslexia. In this study, MWF MRI, intelligence and reading assessments were acquired in twenty participants aged 10-18 years with a wide range of reading ability in order to investigate the relationship between reading ability and myelination. Group comparisons showed markedly lower MWF by 16-69% in poor readers relative to good readers in the left and right thalamus, as well as the left posterior limb of internal capsule, left/right anterior limb of internal capsule, left/right centrum semiovale, and splenium of corpus callosum. MWF over the entire group also correlated positively with three different reading scores in the bilateral thalamus as well as white matter, including the splenium of corpus callosum, left posterior limb of internal capsule, left anterior limb of internal capsule, and left centrum semiovale. MWF imaging from T2 relaxation suggests that myelination particularly in the bilateral thalamus, splenium, and left hemisphere white matter plays a role in reading abilities. Myelin water imaging thus provides a potentially valuable in vivo imaging tool for the study of dyslexia and its remediation.